Answer
The equation in rectangular coordinates:
${\left( {x - 1} \right)^2} + {y^2} + {z^2} = 1$
This is the equation of a sphere of radius $1$ centered at $\left( {1,0,0} \right)$.
![](https://gradesaver.s3.amazonaws.com/uploads/solution/1b612d66-6af5-4219-8bee-a68ea48757d5/result_image/1603324838.gif?X-Amz-Algorithm=AWS4-HMAC-SHA256&X-Amz-Credential=AKIAJVAXHCSURVZEX5QQ%2F20250115%2Fus-east-1%2Fs3%2Faws4_request&X-Amz-Date=20250115T060136Z&X-Amz-Expires=900&X-Amz-SignedHeaders=host&X-Amz-Signature=376356e2a8d1d1346f693a5f5f3323fe86e30f520e45096af6c4fb8e5014b385)
Work Step by Step
In spherical coordinates we have $x = \rho \sin \phi \cos \theta $ and ${\rho ^2} = {x^2} + {y^2} + {z^2}$.
Convert the spherical equation $\rho = 2\cos \theta \sin \phi $ to rectangular coordinates:
$\rho = 2\cos \theta \sin \phi $
$\rho = 2\frac{x}{\rho }$, ${\ \ }$ $2x = {\rho ^2} = {x^2} + {y^2} + {z^2}$
Thus, the spherical equation $\rho = 2\cos \theta \sin \phi $ in rectangular coordinates is
$2x = {x^2} + {y^2} + {z^2}$
${x^2} + {y^2} + {z^2} - 2x = 0$
${\left( {x - 1} \right)^2} - 1 + {y^2} + {z^2} = 0$
${\left( {x - 1} \right)^2} + {y^2} + {z^2} = 1$
This is the equation of a sphere of radius $1$ centered at $\left( {1,0,0} \right)$.